Anti-corruption reform and audit pricing. Issue 4 (2nd October 2017) - Chen, Shenglan; Ma, Hui
Abstract: This paper examines how Chinese anti-corruption reform affects audit pricing. We show that auditors react to the increased audit risk resulting from anti-corruption reform and charge higher audit fees to the politically connected firms. We find that the treatment effect is stronger for firms with poor financial statement quality, with higher operating uncertainty, located in provinces experiencing larger effect of anti-corruption reform, and audited by audit firms with greater bargaining powers. Finally, the results suggest that earnings management and the probability of issuing an unqualified opinion of politically connected firms are reduced after the anti-corruption reform. Our findings provide further insight into the effect of anti-corruption reform on auditors in audit pricing decisions.